Making Interactions Between Domestic and International Students Meaningful - Amos, Yukari Takimoto; Rehorst, Nicole (Journal of International Students, 2018)
The purpose of this practitioner narrative is to identify ways in which meaningful interaction can take place between English learners (ELs) and domestic students in a university setting. In order to learn English effectively, ELs require situations in which they can participate equally in an interaction with a domestic student capable of modifying their English so that it is comprehensible. We created a series of joint classes between teacher candidates and Japanese exchange students in an ESL class. In the class, the first author instructs the teacher candidates on strategies for teaching content to ELs. Second, the teacher candidates teach mini-lessons in their content area to Japanese students. The use of simplified English and visual aids allow ELs to gain confidence and the ability to participate more actively. Third, the Japanese students evaluate the teacher candidates in Japanese. Last, the first author translates the evaluations into English so the teacher candidates can gain meaningful feedback on their performance. The process effectively creates a balance of power that both educates teacher candidates in how to instruct nonnative English speakers and promotes meaningful communication and language growth in ELs. The conditions for meaningful interactions identified in this practice further contribute to the field of effective English learning for international students